Conserved use of tetraspanin CD9 as an entry receptor by rhabdoviruses spanning multiple genera - Wanwan Zhang; Bingbing Sun; Hao Huang; Junyu Chen; Ying’an Liang; Wenxi Li; Qinyu Peng; Ping Zhang; Zhipeng Zhan; Xiaogang Yang; Lan Yao; Huiquan Chen; et al. (Proceedings of the National Academy of Sciences, 2026)
Rhabdoviruses exhibit a broad host range, yet the cellular receptors underlying their cross-species tropism remain poorly defined. Here, we identified tetraspanin CD9 as a conserved functional entry receptor for diverse rhabdoviruses across genera, including viral hemorrhagic septicemia virus (VHSV) ( Novirhabdovirus ), Siniperca chuatsi rhabdovirus (SCRV) ( Siniperhavirus ), and vesicular stomatitis virus (VSV) ( Vesiculovirus ). We demonstrated that the domain IV of VHSV glycoprotein G directly interacted with the large extracellular loop domain of Lateolabrax japonicus CD9 (LjCD9). CD9 knockout, CD9 protein, or CD9 antibody significantly reduced VHSV infection in vitro and CD9 knockout zebrafish, while HEK293T cells, which are nonsusceptible but permissive to VHSV, become susceptible when expressing LjCD9, suggesting that LjCD9 is an entry receptor for VHSV. We further confirmed that LjCD9 functions as a functional receptor of SCRV. Importantly, the human CD9 orthologue can serve as a receptor of VSV. Our findings also revealed that LjCD9 mediated VHSV entry via clathrin- and caveolae-mediated endocytosis. Notably, nitazoxanide (NTZ) was identified as a broad-spectrum inhibitor of VHSV, SCRV, and VSV likely by interfering with the G protein–CD9 interaction. This study establishes CD9 as a cross-species receptor for rhabdoviruses and highlights NTZ as a promising broad-spectrum antiviral agent.